Lo spirito di Arcetri A cento anni dalla nascita dell'Istituto di Fisica dell'Università di Firenze - Mazzoni, Massimo (I libri de «Il Colle di Galileo», 2021)
On 7 November 1921, the new Institute of Physics of the Royal Institute of Higher, Practical and Advanced Studies of Florence was inaugurated in Arcetri. Three years later, with the establishment of the University of Florence, the Degree Course in Physics would start: as such an adventure in research and scientific training began, which would take us to the present day. To mark the centenary of the inauguration of the Institute of Physics in Arcetri, the book takes the opportunity to retrace a part of those years. The period chosen ranged from the arrival of Garbasso in 1913 to the end of the 1960s. The book contains a first part, documenting the history of the Institute of Physics during the above mentioned years. This is followed by a second part, outlining the biographies of some of the protagonists of that history. In the final part, there is an index of the holders of the courses of Physics and Astronomy in Florence from 1876 to 1969. This landscape is the result of research work conducted in the University's Historical Archives of the University.